Internet of things: Applications to developing country agriculture sector - Lalitha, A.; Babu, Suresh Chandra; Purnima, K.S. (Bioinfo Publications, 2018)
The Internet of Things (IoT) is a novel paradigm shift in information technology (IT) sector. The sensor data visualization for agriculture has a great opportunity for mobile technology. Cloud computing offers several applications in the field of agriculture with limited infrastructure and costs. The IoT food supply chains can become self-adaptive systems in which smart objects operate, decide, and learn autonomously. This review paper discusses IoT application in agriculture in developed and developing countries and suggests a conceptual framework for IoT application in State Agricultural Universities of India. By 2020, the world will be having around five billion mobile subscribers and most of these will reside in China and India. Hence, there is a scope for IoT application in Indian agriculture. Any initiative that could move a part of the agriculture and food enterprise into the IoT platform/cloud at a cost-effective price would help the Indian agriculture and food sector.